Menschenrechte wider den Hunger : Das Recht auf Nahrung zwischen Wissenschaft, Politik und globalen Märkten - Kommer, Steffen (Forum Umwelt-, Agrar- und Klimaschutzrecht., 2016)
"What is the contribution social rights can make to overcome the global food crisis? Instead of dismissing a world without hunger as a utopian idea, human rights litigations are described as instruments to accelerate discourses about the causes of food insecurity and the implementation of necessary anti-hunger programs. On the basis of national and international jurisprudence concerning the right to food three aspects of this basic right will be explored: the right to social assistance, the right to a sufficient income and the right to self-sufficiency. Considering increasing global risks such as volatile international food prices and climate change, a transnational dimension of the right to food will be explored. The significance of international human rights discourses will be exemplified based on two case studies concerning the phenomenon of food dumping and the European biofuels policy"--Provided by publisher